Bicuspidization of a unicuspid valve using sliding plasty of a rudimentary right coronary cusp. (29th June 2022) - Shraer, Nathanael; Berrebi, Alain; Biondi, Raoul; Lansac, Emmanuel
Abstract: Unicuspid aortic valve repair relies on the principles of bicuspidization by creating a neo-commissure at 180° from the existing commissure, with pericardial patch interposition. We report a case of a 26-year-old patient with cor triatriatum and a severely regurgitating unicuspid valve. The left atrium membrane was resected. Aortic valve repair was performed creating a neo-commissure using a sliding plasty of the rudimentary right coronary cusp and patch reconstruction of the anterior part of the non-coronary cusp, protected by external subvalvular annuloplasty and hemi-root remodelling. We detail a repair technique of a partial autologous reconstruction approach for bicuspidization. Abstract : A 26-year-old patient was examined for aortic valve repair.